Electron Transport in Nanosystems - Bon a, Janez.; Kruchinin, Sergei. (NATO Science for Peace and Security Series B: Physics and Biophysics, 2009)
The topics discussed at the NATO ARW included the new nanodevice applications, novel materials, mesoscopic superconductivity and biosensors. There have been many significant advances in the past two years and some entirely new directions of research are just opening up. Recent advances in nanoscience have demonstrated that fundamentally new physical phenomena are found when systems are reduced in size with dimensions, comparable to the fundamental microscopic length scales of the investigated material. Recent developments in nanotechnology and measurement techniques now allow experimental investigation of transport properties of nanodevices. Great interest in this research connected with development of spintronics, molecular electronics and quantum information processing.